Slave System Dimension Expansion Approach for Robust Synchronization of Chaotic Systems with Unknown Phase Difference - Huanhuan Mai; Weiwei Zhang; Yapeng Zhao (Journal of Control Science and Engineering)
A technique which increased the dimension of slave system is adopted for robust synchronization of chaotic systems with unknown phase difference. The phase difference plays a great role in variation of dynamic behavior of the coupled systems. The phase difference of the sinusoidal forcing term is always assumed to be known in the majority of the existing literature. However, unknown parameter error value has always existed in real problems. This method uses the properties of the triangular function and increases the number of dimensions in the slave system to match the phase of forcing term in the master system. Numerical simulations show that the flexible control variable we first investigated is very important. We expect our results to be of some broader applicabilities.